Global light industry: Current features and trends. (Journal of Economic Research & Business Administration, 2016)
Over the last decades, the global light industry underwent significant changes that require revision of approaches to planning and management of its development. Thus, it is necessary to take into account current features and global trends when assessing the prospects of the light industry in Kazakhstan. The article presents the results of an analysis of current trends and changes in the light industry. In particular, there are revealed such features as internationalization, clustering, active consolidation of enterprises in the branch. The global economic crisis of 2008 and the subsequent deep recession modified the trend of the light industry, causing a decline in the market, a global transformation of the demand structure, and an offset of the main production centers. Development of the light industry in Kazakhstan requires the use of advanced foreign experience and its adaptation to the current features of the branch.
Keywords: light industry; global market; current trends; global economic crisis; competition.